Geotourism during excursions in the northeastern part of The Gorce National Park - Barmuta, Maria (Geotourism/Geoturystyka)
The Gorce Mountains National Park is located on the southern part of the Małopolska Province in Poland. Despite the lack of spectacular geological attractions it is a very good site to promote Earth Sciences knowledge and especially to educate in geology. The example of the on-day excursion going along the touristic trails within The Gorce Mountains National Park is being described in the presented paper. The author described great diversity of the geological and geomorphological elements, presenting educational values.